The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1007/bf01309472
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic fever with renal syndrome: a study of sequelae following Nephropathia epidemica

Abstract: Sequelae following Nephropathia epidemica (NE) were investigated in 792 individuals living in an endemic area of Sweden. Volunteers were tested for presence of Puumala (PUU) virus specific IgG antibodies in serum, as well as several parameters linked with renal dysfunction and cardiovascular disease (systolic and diastolic blood pressure, ECG, BMI, total cholesterol and serum creatinine). No differences were seen in any of the variables tested between PUU virus antibody positive (n = 110) and negative individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 22 publications
2
16
0
1
Order By: Relevance
“…Due to the frequent occurrence of conspicuous renal failure in the acute phase of hemorrhagic fever with renal syndrome, a possible relation between passed hantavirus infection and the occurrence of chronic renal disease is of interest. Although some circumstantial evidence suggesting such an association has been presented (21-24), a study of 792 persons living in Sweden within an area endemic for nephropathia epidemica showed no difference between seropositive and seronegative persons in several parameters linked to renal dysfunction (25). Moreover, none of 62 patients showed renal sequelae in the follow-up 2 4 years after nephropathia epidemica (25), and, of 66 patients with nephropathia epidemica followed for 6 months after discharge from the hospital, none developed chronically impaired renal function (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the frequent occurrence of conspicuous renal failure in the acute phase of hemorrhagic fever with renal syndrome, a possible relation between passed hantavirus infection and the occurrence of chronic renal disease is of interest. Although some circumstantial evidence suggesting such an association has been presented (21-24), a study of 792 persons living in Sweden within an area endemic for nephropathia epidemica showed no difference between seropositive and seronegative persons in several parameters linked to renal dysfunction (25). Moreover, none of 62 patients showed renal sequelae in the follow-up 2 4 years after nephropathia epidemica (25), and, of 66 patients with nephropathia epidemica followed for 6 months after discharge from the hospital, none developed chronically impaired renal function (26).…”
Section: Discussionmentioning
confidence: 99%
“…Although some circumstantial evidence suggesting such an association has been presented (21-24), a study of 792 persons living in Sweden within an area endemic for nephropathia epidemica showed no difference between seropositive and seronegative persons in several parameters linked to renal dysfunction (25). Moreover, none of 62 patients showed renal sequelae in the follow-up 2 4 years after nephropathia epidemica (25), and, of 66 patients with nephropathia epidemica followed for 6 months after discharge from the hospital, none developed chronically impaired renal function (26). In agreement with these reports, our study showed no significant association between hypertension and the occurrence of antibodies to Puumala virus, and the results of the self-reports, and an analysis of hospital records, presented no evidence of chronic renal disease associated with nephropathia epidemica within the group of seropositive persons.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary function testing reveals persistent defects in carbon monoxide diffusing capacity for up to 1 year and in small airways expiratory flow rates for up to 3 years or more for each of these three viruses, but resolution of symptoms may occur during persistence of the measured deficits. Appearance of proteinuria alone more than 3 years after recovery from SNV infection has been repeatedly documented (Goade, D. unpublished data), contrasting with persistence of urine concentrating capacity, but not proteinuria, for years after HTN and PUU infection (Rubini et al, 1960;Niklasson et al, 1994).…”
Section: Convalescent Phasementioning
confidence: 92%
“…However, subsequent studies have not demonstrated such an association for Puumala in the Netherlands or Sweden [86,98] nor for Seoul or Sin Nombre viruses in Pima Indians [99].…”
Section: Human Diseasementioning
confidence: 99%